A Metropolitan Countryside: Peatland Reclamation and the Birth of a World City. (1st November 2013) - Abrahamse, Jaap Evert; Kosian, Menne
Abstract : In this article, we summarise the results of recent research using 'landscape biography' to examine and explain the landscape of Amstelland, reclaimed from peatland over the past thousand years and now forming the southern periphery of the city of Amsterdam. The landscape biography method has been developed in the Netherlands as a way to integrate landscape research with planning and management. It is a method particularly appropriate to landscape research because of its interdisciplinary basis, its long view of history, its focus on visual data and GIS, and the interactive connection it seeks between expert knowledge and local knowledge. The research led to the publication of a landscape atlas, which by means of a chronological series of maps combined with extensive, illustrated explanation presents in accessible form a landscape-based synthesis of archaeological, archival or historical data. The Atlas is intended not only for planning and research, but also for an ever wider range of stakeholders involved in decision processes affecting these landscapes.